Sex-specific Differences in Response to First-line Helicobacter pylori Eradication Therapy with vonoprazan, amoxicillin, and clarithromycin - Yusaku Kajihara (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Although gender medicine has been promoted in medical research and patient care, limited information is available on sex-specific differences in response to first-line Helicobacter pylori eradication therapy. Therefore, this retrospective study investigated sex-specific differences in response to first-line H. pylori eradication therapy with vonoprazan, amoxicillin, and clarithromycin.Method: The study included 314 patients who received vonoprazan-based triple therapy (20 mg vonoprazan, 750 mg amoxicillin, and 200 or 400 mg clarithromycin; twice daily for 7 days) as first-line H. pylori eradication therapy at Fuyoukai Murakami Hospital from March 1, 2015, to April 30, 2019. First-line eradication rates were determined by intention-to-treat (ITT) and per protocol (PP) analyses. Sex-specific differences in the rate of drug-related treatment-emergent adverse events (TEAEs) were also monitored. Fisher’s exact test was used for identifying sex-specific differences.Results: First-line eradication rates were 95% in ITT and PP analyses regardless of sex, without significant sex-specific differences [ITT analyses: males 95.3% (203/213) vs. females 96.0% (97/101), p = 1.0; PP analyses: males 95.3% (203/213) vs. females 96.0% (95/99), p = 1.0]. However, the rate of drug-related TEAEs was significantly higher in females than in males [males 4.2% (9/213) vs. females 17.8% (18/101), p 0.001]. In particular, skin rash occurred only in females [males 0% (0/213) vs. females 10.9% (11/101), p 0.00001].Conclusion: Females experienced more drug-related TEAEs than males during first-line H. pylori eradication therapy with vonoprazan-based triple therapy. In particular, skin rash was observed only in females.